Two feet, four paws the girl who walked her dog 4,500 miles - Talbot-Ponsonby, Spud. (Chichester Summersdale, 1999)
Take one feisty girl, a dog and a camper van called "Spudtruck" and set them off on a journey around Britain's coastline, the equivalent distance of London to Calcutta, to raise almost 44,000 for the charity "Shelter", and revel in the honest descriptions of the true state of our island.
Originally published: 1996.
UCWS-3248g donated by Adrienne Maguddayao -February 2017
Keywords: Talbot-Ponsonby, Spud -- Travel -- Great Britain; Walking -- Great Britain; Coasts -- Great Britain; Dogs -- Great Britain; Great Britain -- Description and travel